Analisa Efisiensi Thermal Pembangkit Listrik Tenaga Panas Bumi Lahendong Unit 5 Dan 6 Di Tompaso - Gerry A. Kusuma; Glanny Mangindaan; Marthinus Pakiding (Universitas Sam Ratulangi, 2018)
Abstract— A geothermal power plant (PLTP) is a plant that uses vapor in the earth as the main energy. Vapor which in the earth is supplied from production well through steam transmission system which then passing steam receiving header. When there is excessive pressure in the steam receiver, then the steam will be dump away to Vent Structure. Steam then get flowed to the Separator which serves to separate the vapor with water. The separation water is called brine. Brine from separator is streamed to the settling basin. Then vapor comes in to the Scrubber, which serves to separate moisture that contained in vapor, so then the vapor is expected clean and dry, which will be include in the steam turbine. A geothermal power plant (PLTP) especially PLTP 5 and 6 Lahendong are the new built geothermal power plant as part of the 35.000 MW program from the government. Therefore need to know how much the thermal efficiency that contain in the power plant and how to increase its efficiency. This research will discuss thermal efficiency analysis of PLTP 5 and 6 Lahendong through state level analysis with a thermodynamic approach and analysis in each process of the plant.Keywords: Geothermal Plant, Thermal Efficiency, Thermodynamic, Vapor.Abstrak— Pembangkit Listrik Tenaga Panas Bumi (PLTP) adalah pembangkit yang menggunakan energi panas dari dalam bumi. Uap panas dari dalam perut bumi di suplai dari sumur produksi melalui sisterm transmisi uap yang kemudian melewati steam receiving header. Bila terjadi tekanan berlebih di dalam steam receiver maka uap akan dibuang melalui Vent Structure. Dari Steam Header uap kemudian dialirkan ke separator yang berfungsi untuk memisahkan uap dengan air. Air hasil pemisahan tersebut disebut brine. Brine dari separator tersebut kemudian dialirkan meuju ke kolam pengendapan atau Settling Basin. Kemudian uap masuk ke Scrubber, yang berfungsi untuk memisahkan moisture yang terkandung dalam uap, sehingga diharapkan uap bersih dan kering yang akan masuk ke dalam Turbin uap. Pembangkit Listrik Tenaga Panas Bumi (PLTP) khususnya PLTP 5 dan 6 Lahendong merupakan unit pembangkit yang baru dibangun sebagai bagian dari program 35.000 MW dari pemerintah. Sebab itu perlu diketahui berapa besar efisiensi thermal yang terdapat di pembangkit tersebut dan cara peningkatan efisiensinya. Penelitian ini akan membahas analisa efisiensi thermal dari PLTP 5 dan 6 Lahendong melalui analisa tingkat keadaan dengan pendekatan termodinamika dan analisa di tiap proses pembangkit tersebut. Kata Kunci : Efisiensi Thermal, PLTP, Termodinamika, Uap Panas